History of luminescence - del Castillo García, Benito (Circumscribere International Journal for the History of Science, 2012)
The present article discusses the processes of molecular photoluminescence (fluorescence and phosphorescence) in pharmaceutical analysis within the context of the advancement of chemistry and instrumental analysis to illustrate the trajectory of that set of spectroscopic techniques.